2006
DOI: 10.1016/j.febslet.2006.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of protein kinase CKII is associated with cellular senescence

Abstract: Protein kinase CKII (CKII) plays a critical role in cell growth and proliferation. In this study, we examine how CKII activity is regulated during cellular senescence. Our results demonstrate that CKII activity apparently decreases during both replicative and H 2 O 2 -induced senescence in human diploid fibroblast IMR-90 cells. The mRNA and protein levels of CKIIa decreases significantly during replicative and H 2 O 2 -induced senescence, while only slight reduction in those of CKIIb is observed during replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
9
43
0
1
Order By: Relevance
“…One of the unusual outcomes was that the flavonoid API, used successfully here and elsewhere [19] to induce renal cell senescence, also caused increased lipid peroxidation (increased MDA), decreased TAC and the greatest mitochondrial dysfunction with or without concurrent H 2 O 2 . Lagoa et al [24] recently reported, using mitochondria isolated from rat brain and heart, that API (10 μ M ) inhibited the activity of Complex I of the electron transport chain by affecting the binding of the coenzyme substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the unusual outcomes was that the flavonoid API, used successfully here and elsewhere [19] to induce renal cell senescence, also caused increased lipid peroxidation (increased MDA), decreased TAC and the greatest mitochondrial dysfunction with or without concurrent H 2 O 2 . Lagoa et al [24] recently reported, using mitochondria isolated from rat brain and heart, that API (10 μ M ) inhibited the activity of Complex I of the electron transport chain by affecting the binding of the coenzyme substrate.…”
Section: Discussionmentioning
confidence: 99%
“…After dose-response studies (unpublished data), they were grown to 80-90% confluence and then treated for 18-24 h with 0.4 m M H 2 O 2 for oxidative stress, and 100 µ M apigenin (API) to induce renal cell senescence [19]. DMSO as a vehicle control was <1% in growth medium).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, overexpression of CKIIα in the T cells of transgenic mice results in a high predisposition for lymphoma formation (Seldin and Leder, 1995). Our own previous data indicated an association between the decrease in CKII activity by down-regulation of CKIIα transcription and progressing cellular senescence (Ryu et al, 2006). In the present study, we demonstrate for the first time that CKIIα' is also down-regulated transcriptionally in senescent cells.…”
Section: Resultsmentioning
confidence: 68%
“…We have previously demonstrated that the levels of CKIIα protein and mRNA decrease in IMR-90 cells during senescence (Ryu et al, 2006). Epigenetic modifications, such as DNA methylation, have emerged as important mechanisms to silence genes (Bird, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation